Oxidation leaching method

JP2025504678APending Publication Date: 2025-02-14BASF SE
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024545027
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2022-02-01
Filing Date
2023-01-31
Publication Date
2025-02-14

AI Technical Summary

Benefits of technology

が実証される(実施例5)。対照的に、反応の開始時にCAMを添加すると(実施例6)、発生した水素によるCAMの部分的な還元に起因して、CAMによる銅酸化の効率が低下し得る。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025504678000001_ABST
    Figure 2025504678000001_ABST
Patent Text Reader

Abstract

A method for leaching a material containing copper in the zero oxidation state, comprising contacting the material with an aqueous acidic solution having a pH of less than 6 to form a leach mixture, and leaching the copper to a solution of the formula Li p M q M' r O s where M comprises one or more metals selected from nickel, manganese, and cobalt, M' comprises one or more metals selected from Mg, Ca, Ba, Al, Ti, Zr, Zn, Fe, V, Mo, and W, p is in the range of 1 to 1.4, q is in the range of 0.6 to 2, r is in the range of 0 to 1, s is in the range of 2 to 4, and the total amount of copper, in moles, present in the material prior to leaching is divided by the total amount of oxidizing agent, in moles. [0010] TIFF2025504678000040.tif12150 range, [0025] TIFF2025504678000041.tif10150, and [0030] TIFF2025504678000042.tif6150 is the average oxidation number of M', determined by calculating the molar average of the most stable oxidation number of each metal as an oxide contained in M'.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The project leading to this application has received funding from the Bundesministerium für Wirtschaft und Klimaschutz (DE;FKZ:16BZF101A) and any disclosures herein are the sole responsibility of the applicant.

[0002] A method for leaching a material containing copper in the zero oxidation state, comprising contacting the material with an aqueous acidic solution having a pH of less than 6 to form a leach mixture, and leaching the copper to a concentration of 0.05% by weight of the formula Li p M q M' r O s Also disclosed is a method for recycling at least one battery material selected from lithium ion batteries, lithium ion battery waste, lithium ion battery manufacturing scrap, lithium ion cell manufacturing scrap, lithium ion cathode active materials, and combinations thereof. Also disclosed is a method for recycling at least one battery material selected from lithium ion batteries, lithium ion battery waste, lithium ion battery manufacturing scrap, lithium ion cell manufacturing scrap, lithium ion cathode active materials, and combinations thereof. p M q M' r O s Also disclosed is a method for reducing a first material represented by the formula: with a second material comprising copper in the zero oxidation state. [Background technology]

[0003] High purity lithium is a valuable resource. Many sources of lithium, such as lithium ion batteries, lithium ion battery waste, lithium-containing water, such as groundwater, and lithium-containing raw ores, are complex mixtures of various elements and compounds. Removal and purification of lithium from materials, such as lithium ion battery materials, is an exemplary step in the recycling of lithium ion batteries. Lithium ion battery materials are complex mixtures of various elements and compounds, and it may be desirable to remove various non-lithium impurities. Such impurities may exist in various oxidation states, which may affect, for example, the efficiency of the leaching process. For example, in some leaching processes, metals in high oxidation states may be leached more or less efficiently than metals in low or zero oxidation states. Non-lithium impurities are also valuable resources, and it may be further desirable to separate and purify various elements and compounds from such materials.

[0004] Thus, there is a need for methods for removing lithium from materials, e.g., battery materials, and for recycling lithium-ion battery materials. For example, there is a need for leaching methods that efficiently and effectively leach complex mixtures of elements and compounds, e.g., mixed metals coexisting in various oxidation states. For example, there is a need for economical methods that provide high lithium recovery and high lithium purity. There is also a need for economical methods that provide high recovery and high purity for removing valuable metals, e.g., copper, from materials.

[0005] CN111961839A discloses a method for leaching valuable metals from the negative and positive active materials of used lithium ion batteries and simultaneously removing impurities. The method specifically includes the steps of roasting the negative and positive active materials of used lithium ion batteries to remove part of the impurities F and P, treating the roasted material after roasting with a two-stage acid leaching method to leach valuable metals and remove most of the F, and treating the leachate with a chemical method to remove Fe, Al, Cu, and the remaining F, P, and other impurities. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] CN111961839A Summary of the Invention [Problem to be solved by the invention]

[0007] The present invention provides a method for removing lithium and impurities from materials such as battery materials, a method for recycling lithium ion battery materials, and an economical leaching method with high metal recovery and high metal purity. [Means for solving the problem]

[0008] A method for leaching a material containing copper in the zero oxidation state, comprising contacting the material with an aqueous acidic solution having a pH of less than 6 to form a leach mixture, and leaching the copper to a concentration of 0.05% by weight of the formula Li p M q M' r O s where M comprises one or more metals selected from nickel, manganese, and cobalt, M' comprises one or more metals selected from Mg, Ca, Ba, Al, Ti, Zr, Zn, Fe, V, Mo, and W, p is in the range of 1 to 1.4, q is in the range of 0.6 to 2, r is in the range of 0 to 1, s is in the range of 2 to 4, and the total amount of copper, in moles, present in the material prior to leaching is divided by the total amount of oxidizing agent, in moles.

number

number

number

[0009] Also disclosed is a method for recycling at least one battery material selected from lithium ion batteries, lithium ion battery waste, lithium ion battery manufacturing scrap, lithium ion cell manufacturing scrap, lithium ion cathode active material, and combinations thereof, the method comprising optionally heat treating the at least one battery material at a temperature in the range of 350° C. to 900° C., mechanically crushing the at least one battery material to obtain a black mass, optionally classifying the black mass to obtain a fine fraction and a coarse fraction, and subjecting the black mass, and optionally the fine fraction, the coarse fraction, or the fine fraction and the coarse fraction, to a leaching method as disclosed herein.

[0010] Also, the formula Li p M q M' r O s Also disclosed is a method for reducing a first material represented by the formula: with a second material comprising copper in a zero oxidation state, the method comprising the steps of contacting the first material with an acidic aqueous solution having a pH of less than 6 to form a mixture; and reducing the first material with the second material, wherein M comprises one or more metals selected from nickel, manganese, and cobalt; M' comprises one or more metals selected from Mg, Ca, Ba, Al, Ti, Zr, Zn, Fe, V, Mo, and W; p is in the range of 1 to 1.4; q is in the range of 0.6 to 2; r is in the range of 0 to 1; s is in the range of 2 to 4; and the total amount of copper, expressed in moles, present in the second material prior to the reduction step is divided by the total amount of the first material, expressed in moles.

number

number

number

[0011] [Figure 1] FIG. 1 illustrates an exemplary batch process consistent with certain embodiments of the present disclosure. [Diagram 2] FIG. 2 illustrates an exemplary continuous process consistent with certain embodiments of the present disclosure. [Diagram 3] FIG. 3 shows the XRD pattern of an exemplary black mass. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] A method for leaching a material containing copper in the zero oxidation state, comprising contacting the material with an aqueous acidic solution having a pH of less than 6 to form a leach mixture, and leaching the copper to a concentration of 0.05% by weight of the formula Li p M q M' r O s where M comprises one or more metals selected from nickel, manganese, and cobalt, M' comprises one or more metals selected from Mg, Ca, Ba, Al, Ti, Zr, Zn, Fe, V, Mo, and W, p is in the range of 1 to 1.4, q is in the range of 0.6 to 2, r is in the range of 0 to 1, s is in the range of 2 to 4, and the total amount of copper, in moles, present in the material before leaching is divided by the total amount of oxidizing agent, in moles.

number

number

number

[0013] In some embodiments,

[0014] [Number] is in the range of.

[0015] In some embodiments, the oxidizing agent contains lithium nickel cobalt manganese oxide represented by the formula Li (1+x) (Ni a Co b Mn c M ’ d ) (1-x) O2, where M ’ is selected from Mg, Ca, Ba, Al, Ti, Zr, Zn, Mo, V and Fe, 0 ≤ x ≤ 0.2, 0.1 ≤ a ≤ 0.95, 0 ≤ b ≤ 0.9, or 0.05 < b ≤ 0.5, 0 ≤ c ≤ 0.6, 0 ≤ d ≤ 0.1, and a + b + c + d = 1.

[0016] In some embodiments, the oxidizing agent contains lithium nickel cobalt aluminum oxide represented by the formula Li[Ni h Co i Al j O 2+t where h is in the range of 0.8 to 0.95, i is in the range of 0.1 to 0.3, j is in the range of 0.01 to 0.10, and t is in the range of 0 to 0.4.

[0017] In some embodiments, the oxidizing agent contains lithium manganese oxide represented by the formula Li (1+x) Mn 2-x-y-z M y M ’ z O4, where x is in the range of 0 to 0.2, y + z is in the range of 0 to 0.1, and M ’ is selected from Al, Mg, Fe, Ti, V, Zr and Zn.

[0018] In some embodiments, the oxidizing agent is a compound represented by the formula xLi (1+1 / 3) M (2 / 3) O2·yLiMO2·zLiM’O2, where M in the formula includes at least one metal of Mn, Ni, and Co in an oxidation state of +4, M’ is at least one transition metal, and 0 < x < 1, 0 < y < 1, 0 < z < 1, and x + y + z = 1.

[0019] In some embodiments, the material is a black mass from a lithium-ion battery material, and the oxidizing agent is a cathode active material.

[0020] In some embodiments, at least 50% of the oxidizing agent is added to the leaching mixture after the contacting step, and optionally, during the contacting step, hydrogen gas is generated and after the hydrogen gas generation rate is reduced to 10% of the maximum hydrogen gas generation rate during the contacting step, at least 50% of the oxidizing agent is added to the leaching mixture.

[0021] In some embodiments, the cathode active material oxidizes 50% - 100% of the copper.

[0022] In some embodiments, the method further includes adding an additional oxidizing agent selected from O2, N2O, hydrogen peroxide, and peroxodisulfate to the leaching mixture, and optionally, during the contacting step, hydrogen gas is generated and after the hydrogen gas generation rate is reduced to 10% of the maximum hydrogen gas generation rate during the contacting step, the additional oxidizing agent is added to the leaching mixture.

[0023] In some embodiments, the method further includes adding a reducing agent selected from SO2, metabisulfite, bisulfite, dithionate, thiosulfate, H2O2, and H2 to the leaching mixture, and optionally, the reducing agent is added after at least 50% of the copper has been oxidized.

[0024] In some embodiments, the acidic aqueous solution comprises at least one acid selected from H2SO4, methanesulfonic acid, and nitric acid.

[0025] In some embodiments, the acidic aqueous solution has an acid concentration in the range of 18 mol / L to 0.0001 mol / L.

[0026] In some embodiments, the material comprises 0.1% to 10% by weight copper, based on the total weight of the material.

[0027] In some embodiments, the methods disclosed herein provide an aqueous solution containing metal ions, and the metal ions are separated to provide at least one essentially pure metal ion solution and / or at least one essentially pure solid metal ion salt.

[0028] definition As used herein, "a" or "an" entity refers to one or more of that entity; for example, "a compound" refers to one or more compounds or at least one compound, unless otherwise specified. Thus, the terms "a" (or "an"), "one or more," and "at least one" are used interchangeably herein.

[0029] As used herein, the term "material" refers to elements, components, and / or substances that make up or can make something.

[0030] As used herein, a "reducing agent" is a compound capable of reducing metal oxides and / or metal hydroxides. For example, some reducing agents are capable of reducing some metal oxides and / or some metal hydroxides but not others.

[0031] As used herein, an "oxidizing agent" is a compound capable of oxidizing a metal in the zero oxidation state. For example, some oxidizing agents can oxidize some metals in the zero oxidation state, but not others.

[0032] As used herein, a "solution" is a combination of a fluid and one or more compounds, for example, each of the one or more compounds in a solution may or may not be dissolved in the fluid.

[0033] As used herein, an "essentially pure metal ion solution" is a solution comprising metal ions, counterions, and a solvent, where the total weight of the metal ions and counterions is at least 50% by weight, excluding the weight of the solvent.

[0034] As used herein, an "essentially pure solid metal ion salt" is a solid comprising a metal ion and a counterion, where the total mass of the metal ion and counterion is at least 50% by weight of the solid, excluding the mass of the solvent.

[0035] As used herein, the term "sparging" refers to the dispersion of a gas through a liquid.

[0036] As used herein, the term "base" refers to a material that can react with hydronium ions to increase the pH value of an acidic solution.

[0037] The term "standard electrode potential" as used herein has its general application in the field of electrochemistry and is the value of the electromotive force of an electrochemical cell at 1 bar and 298.15 K where hydrogen molecules are oxidized to solvated protons at the standard hydrogen electrode. The potential of the standard hydrogen electrode is, by definition, zero volts. An exemplary reference is: Johnstone, AH "CRC Handbook of Chemistry and Physics - 69th Edition Editor in Chief RC Weast, CRC Press Inc., Boca Raton, Florida, 1988.

[0038] material: In some embodiments, the material comprises copper in the zero oxidation state. In some embodiments, the material comprises 0.1% to 30% by weight copper, based on the total weight of the material. In some embodiments, the material comprises 0.1% to 20% by weight copper, based on the total weight of the material. In some embodiments, the material comprises 0.1% to 10% by weight copper, based on the total weight of the material. In some embodiments, the material comprises 1% to 10% by weight copper, based on the total weight of the material.

[0039] In some embodiments, the material comprises 0.1% to 30% by weight lithium based on the total weight of the material. In some embodiments, the material comprises 1% to 20% by weight lithium based on the total weight of the material. In some embodiments, the material comprises 5% to 20% by weight lithium based on the total weight of the material.

[0040] In some embodiments, the material is a lithium ion battery material, such as black lumps. In some embodiments, the material comprises a lithium ion battery material, such as black lumps.

[0041] In some embodiments, the material comprises one or more selected from nickel, cobalt, manganese, and combinations thereof.

[0042] In some embodiments, the material further comprises one or more metals in a zero oxidation state selected from nickel, cobalt, aluminum, iron, manganese, rare earth metals, and combinations thereof.

[0043] In some embodiments, the material includes 0.1 weight percent to 10 weight percent lithium, 0 weight percent to 60 weight percent nickel, 0 weight percent to 20 weight percent cobalt, 0 weight percent to 20 weight percent copper, 0 weight percent to 20 weight percent aluminum, 0 weight percent to 20 weight percent iron, and 0 weight percent to 20 weight percent manganese, each weight percent based on the total weight of the material.

[0044] In some embodiments, the material or a precursor thereof is pyrolyzed prior to leaching, hi some embodiments, pyrolysis is carried out under an inert atmosphere, an oxidizing atmosphere, a reducing atmosphere, or a combination thereof.

[0045] "Black chunk" refers to material that contains lithium, e.g., from lithium ion batteries, lithium ion battery waste, lithium ion battery manufacturing scrap, lithium ion cell manufacturing scrap, lithium ion active cathode material, and / or combinations thereof, by mechanical processes, e.g., mechanical grinding. For example, black chunk can be derived from battery scrap, which is mechanically processed to obtain active components of electrodes, e.g., graphite and active cathode material, and can include impurities from casings, electrode foils, cables, separators, and electrolytes. In some examples, the battery scrap can be subjected to heat treatment to pyrolyze organic (e.g., electrolyte) and polymer (e.g., separator and binder) materials. Such heat treatment can be performed before or after mechanical grinding of the battery materials. In some embodiments, the black chunk is subjected to heat treatment.

[0046] Lithium-ion batteries may be disassembled, punched, pulverized, for example in a hammer mill, rotor mill, and / or shredded, for example in an industrial shredder. From this type of mechanical process, the active material of the battery electrodes is obtained. Light fractions such as organic plastics and housing parts made of aluminum or copper foil may be removed, for example, by forced gas flow, air separation, or classification or sieving.

[0047] Battery scrap can come from, for example, used batteries or from manufacturing waste, such as off-spec material. In some embodiments, the material is obtained from mechanically processed battery scrap, such as battery scrap processed in a hammer mill, rotor mill, or industrial shredder. Such material has an average particle size (D50) in the range of 1 μm to 1 cm, such as 1 μm to 500 μm, and further such as 3 μm to 250 μm.

[0048] Larger parts of the battery scrap, such as housings, wires and electrode support films, may be mechanically separated to allow the corresponding materials to be removed from the battery material used in the method. In some embodiments, separation is performed by manual or automatic sorting. For example, magnetic parts can be separated by non-magnetic metal magnetic separation with an eddy current separator. Other techniques include fixtures and air tables.

[0049] The mechanically treated battery scrap may be subjected to a solvent treatment to dissolve and separate the polymer binders used to bind the transition metal oxides to the current collector film or, for example, to bind graphite to the current collector film. Suitable solvents are N-methylpyrrolidone, N,N-dimethyl-formamide, N,N-dimethylacetamide, N-ethylpyrrolidone and dimethylsulfoxide in pure form, as a mixture of at least two of the following, or as a mixture with 1% to 99% water by weight.

[0050] In some embodiments, the mechanically treated battery scrap may be subjected to heat treatment in a wide range of temperatures under various atmospheres. In some embodiments, the temperature ranges from 100° C. to 900° C. In some embodiments, lower temperatures below 300° C. serve to evaporate residual solvent from the battery electrolyte, higher temperatures decompose the binder polymer, and temperatures above 400° C. may change the composition of the inorganic materials as some of the transition metal oxides are reduced by carbon contained in the scrap material or by introducing a reducing gas. In some embodiments, reduction of lithium metal oxide is avoided by keeping the temperature below 400° C. and / or by removing the carbonaceous material before heat treatment.

[0051] In some embodiments, the heat treatment is performed at a temperature in the range of 350° C. and 900° C. In some embodiments, the heat treatment is performed at a temperature in the range of 450° C. to 800° C. In some embodiments, the heat treatment is performed under an inert, oxidizing, or reducing atmosphere. In some embodiments, the heat treatment is performed under an inert or reducing atmosphere. In some embodiments, a reducing agent is formed from the pyrolyzed organic (polymer) components under the conditions of the heat treatment. In some embodiments, a reducing agent is formed by the addition of a reducing gas, such as H2 and / or CO.

[0052] In some embodiments, the material includes nickel, cobalt, manganese, copper, aluminum, iron, phosphorous, or combinations thereof.

[0053] In some embodiments, the material has a mass ratio of lithium to the total mass of nickel, cobalt, manganese, copper, aluminum, iron, and phosphorus in the range of 0.01 to 10. In some embodiments, the material has a mass ratio of lithium to the total mass of nickel, cobalt, manganese, copper, aluminum, iron, and phosphorus in the range of 0.01 to 5. In some embodiments, the material has a mass ratio of lithium to the total mass of nickel, cobalt, manganese, copper, aluminum, iron, and phosphorus in the range of 0.01 to 2. In some embodiments, the material has a mass ratio of lithium to the total mass of nickel, cobalt, manganese, copper, aluminum, iron, and phosphorus in the range of 0.01 to 1.

[0054] In some embodiments, a method for recycling lithium ion battery materials includes mechanically grinding at least one selected from lithium ion batteries, lithium ion battery waste, lithium ion battery manufacturing scrap, lithium ion cell manufacturing scrap, lithium ion active cathode material, and combinations thereof to obtain black mass.

[0055] Oxidizer: In some embodiments, the oxidizing agent has the formula Li p Mq M’ r O s is represented by

[0056] In some embodiments, M comprises one or more metals selected from nickel, manganese, and cobalt, M’ comprises one or more metals selected from Mg, Ca, Ba, Al, Ti, Zr, Zn, Fe, V, Mo, and W, p ranges from 1 to 1.4, q ranges from 0.6 to 2, r ranges from 0 to 1, and s ranges from 2 to 4.

[0057] In some embodiments, the oxidizing agent is lithium (1+x) (Ni a Co b Mn c M ’ d ) (1-x) O2-containing lithium nickel cobalt manganese oxide, where M ’ is selected from Mg, Ca, Ba, Al, Ti, Zr, Zn, Mo, V, and Fe, 0 ≤ x ≤ 0.2, 0.1 ≤ a ≤ 0.95, 0 ≤ b ≤ 0.9, or 0.05 < b ≤ 0.5, 0 ≤ c ≤ 0.6, 0 ≤ d ≤ 0.1, and a + b + c + d = 1.

[0058] In some embodiments, the oxidizing agent is lithium [Ni h Co i Al j O 2+t containing lithium nickel-cobalt-aluminum oxide, where h ranges from 0.8 to 0.95, i ranges from 0.1 to 0.3, j ranges from 0.01 to 0.10, and t ranges from 0 to 0.4.

[0059] In some embodiments, the oxidizing agent is lithium (1+x) Mn 2-x-y-z M y M ’ z containing lithium manganese oxide represented by O4, where x ranges from 0 to 0.2, y + z ranges from 0 to 0.1, and M ’is selected from Al, Mg, Fe, Ti, V, Zr, and Zn.

[0060] In some embodiments, the oxidizing agent is of the formula xLi (1+1 / 3) M (2 / 3) O2·yLiMO2·zLiM’O2, where M includes at least one metal of Mn, Ni, Co in an oxidation state of +4, M’ is at least one transition metal, and 0 < x < 1, 0 < y < 1, 0 < z < 1, and x + y + z = 1.

[0061] In some embodiments, the oxidizing agent is a cathode active material.

[0062] In some embodiments, the oxidizing agent includes at least one cathode active material selected from lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium manganese oxide, lithium-ion battery scrap containing cathode active materials such as manufacturing waste from the production of cathode active materials, and combinations thereof.

[0063] In some embodiments, the lithiated metal oxide is used as part of a mixture as an oxidizing agent. For example, the black mass may contain a cathode active material. In some embodiments, the amount of the cathode active material in the black mass can be determined by methods known in the art. For example, the amount of the cathode active material can be determined by XRD with Rietveld refinement that enables quantitative evaluation of the amount of NCM. Another method is, for example, redox titration, where the material is reacted with a reducing agent, such as potassium iodide, in the reaction: Li p M q M’ r O s +n(e M )J - +2sH + →pLi++qM 2+ +rM’ (OxM’)+ +0.5n(e M )I2+sH2O, and the amount of iodine produced is determined by titration with, for example, sodium thiosulfate, and n(e M) can be evaluated.

[0064] In some embodiments where the lithiated metal oxide is, for example, part of a mixture with a black mass, the mixture contains only a limited amount of a material capable of reducing the lithiated metal oxide other than copper in the zero oxidation state. For example, in some embodiments where the lithiated metal oxide is part of the mixture, the molar ratio of the non - copper material capable of reducing the lithiated metal oxide to copper in the zero oxidation state is lower than 3:1, for example lower than 1:1, for example lower than 1:4. In some embodiments, the non - copper material capable of reducing the lithiated metal oxide contains organic compounds such as alcohols, aldehydes, carboxylic acids, esters, and / or acetals that form the corresponding aldehyde, ketone, carboxylic acid, or carbon dioxide upon oxidation. For example, the black mass may contain residual components of the battery electrolyte solvent. In some embodiments, the amount of the non - copper reducing material is less than 20 w%, or less than 10 w%, or less than 5 w% of the mixture.

[0065] In some embodiments, the oxidizing agent contains lithium nickel cobalt manganese oxide represented by the formula Li 1+x (Ni a Co b Mn c M 1 d ) 1-x O2, where M 1 is selected from Mg, Ca, Ba, Al, Ti, Zr, Zn, Mo, V and Fe, 0 ≤ x ≤ 0.2, 0.1 ≤ a ≤ 0.95, 0 ≤ b ≤ 0.9 (for example 0.05 < b ≤ 0.5), 0 ≤ c ≤ 0.6, 0 ≤ d ≤ 0.1, and a + b + c + d = 1. Exemplary lithium nickel cobalt manganese oxides include Li (1+x) [Ni 0.33 Co 0.33 Mn 0.33 (1-x) O2, Li (1+x) [Ni 0.5 Co 0.2 Mn 0.3 (1-x) ​​O2, Li (1+x) [Ni 0.6 Co 0.2 Mn 0.2 ] (1-x) O2, Li (1+x) [Ni 0.7 Co 0.2 Mn 0.3 ] (1-x) O2, Li (1+x) [Ni 0.8 Co 0.1 Mn 0.1 ] (1-x) O2, and Li[Ni 0.85 Co 0.13 Al 0.02 ]O2 is included.

[0066] In some embodiments, the oxidizing agent has the formula Li[Ni h Co i Al j ]O 2+t wherein h is in the range of 0.8 to 0.95, i is in the range of 0.1 to 0.3, j is in the range of 0.01 to 0.10, and t is in the range of zero to 0.4.

[0067] In some embodiments, the oxidant is Li x The compound includes MO2, where x is an integer greater than or equal to 1, and M is selected from metals, transition metals, rare earth metals, and combinations thereof. In some embodiments, the oxidizing agent has the formula Li (1+x) Mn 2-x-y-z M y M ’ z O4, where x is in the range of zero to 0.2, y+z is in the range of zero to 0.1, and M ’ is selected from Al, Mg, Fe, Ti, V, Zr and Zn.

[0068] In some embodiments, the oxidizing agent has the formula xLi (1+1 / 3) M (2 / 3)A compound represented by O2·yLiMO2·zLiM’O2, where M in the formula contains at least one metal of Mn, Ni, Co in an oxidation state of +4, M’ is at least one transition metal, and 0 < x < 1, 0 < y < 1, 0 < z < 1 and x + y + z = 1.

[0069] In some embodiments, the additional oxidizing agent is an acid, such as H2SO4, HNO3, and combinations thereof. In some embodiments, the oxidizing agent is not an acid, such as O2, N2O, and combinations thereof.

[0070] In some embodiments, the additional oxidizing agent has a standard electrode potential in the range of +0.1V to +1.5V. In some embodiments, the oxidizing agent has a standard electrode potential in the range of +0.4V to +1.3V. In some embodiments, the oxidizing agent has a standard electrode potential in the range of +1V to +1.5V.

[0071] Reducing agent: In some embodiments, the reducing agent is one or more selected from SO2, metabisulfite, bisulfite, dithionate, thiosulfate, H2O2, H2, and combinations thereof.

[0072] In some embodiments, the reducing agent has a standard electrode potential in the range of +1V to -0.5V. In some embodiments, the reducing agent has a standard electrode potential in the range of +0.2V to -0.3V.

[0073] Hydrogen peroxide functions as a reducing agent or an oxidizing agent depending on the reaction partner. The possible oxidation and reduction reactions are: H2O2 → O2 + 2e - +2H + and H2O2 + 2e - +2H + → 2H2O. In some embodiments, the standard electrode potential of the reaction partner affects which reaction occurs. For example, under certain conditions, permanganate (MnO4 - ) is reduced by hydrogen peroxide, while on the other hand, Fe 2+In some embodiments, the formation of water involves the oxidation of H + is required, more acidic conditions favor the oxidation reaction, and H + is generated during the reaction, less acidic conditions favor the reduction reaction. In some embodiments, the following reactions may or may not occur depending on the metal(s) M and the conditions used: 2LiMO2+H2O2+3H2SO4→2LiSO4+2MSO4+4H2O+O2, and M+H2O2+H2SO4→MSO4+2H2O.

[0074] Acidic aqueous solution: In some embodiments, the acidic aqueous solution comprises at least one acid selected from H2SO4, methanesulfonic acid, and nitric acid.

[0075] In some embodiments, the acidic aqueous solution has an acid concentration in the range of 18 mol / L to 0.0001 mol / L. In some embodiments, the acidic aqueous solution has an acid concentration in the range of 18 mol / L to 0.001 mol / L. In some embodiments, the acidic aqueous solution has an acid concentration in the range of 18 mol / L to 0.01 mol / L. In some embodiments, the acidic aqueous solution has an acid concentration in the range of 18 mol / L to 0.1 mol / L. In some embodiments, the acidic aqueous solution has an acid concentration in the range of 18 mol / L to 1 mol / L. In some embodiments, the acidic aqueous solution has an acid concentration in the range of 10 mol / L to 0.0001 mol / L. In some embodiments, the acidic aqueous solution has an acid concentration in the range of 1 mol / L to 0.0001 mol / L. In some embodiments, the acidic aqueous solution has an acid concentration in the range of 10 mol / L to 1 mol / L.

[0076] In some embodiments, the acidic aqueous solution comprises at least one selected from H2SO4, O2, N2O, and combinations thereof. In some embodiments, the acidic aqueous solution comprises H2SO4. In some embodiments, the acidic aqueous solution comprises one or more acids selected from H2SO4, CH3SO3H, HNO3, and combinations thereof. In some embodiments, the acidic aqueous solution further comprises one or more selected from O2, N2O, and combinations thereof. In some embodiments, the only oxidizing agent added to the acidic aqueous solution is an oxidizing agent having the formula Li p M q M' r O s In some embodiments, the acidic aqueous solution includes an acid that is also an oxidizing agent, such as H2SO4. In some embodiments, the acidic aqueous solution includes an oxidizing agent that is not an acid, such as O2, N2O, or a combination thereof. In some embodiments, the acidic aqueous solution includes an acid and an oxidizing agent. In some embodiments, the acidic aqueous solution includes an acid and an oxidizing agent. p M q M' r O s In some embodiments, the acidic aqueous solution includes an acid that is also an oxidizing agent, and further includes an oxidizing agent that is not an acid.

[0077] Leaching Method: In some embodiments, a method is provided for leaching a material containing zero oxidation state copper, the method comprising contacting the material with an acidic aqueous solution having a pH of less than 6 to form a leach mixture, and reacting the material with an acidic aqueous solution having a pH of less than 6 to form a leach mixture having a formula Li p M q M' r O swherein M comprises one or more metals selected from nickel, manganese, and cobalt, M' comprises one or more metals selected from Mg, Ca, Ba, Al, Ti, Zr, Zn, Fe, V, Mo, and W, p is in the range of 1 to 1.4, q is in the range of 0.6 to 2, r is in the range of 0 to 1, s is in the range of 2 to 4, and the total amount of copper, in moles, present in the material before leaching is divided by the total amount of oxidizing agent, in moles.

number

number

number

[0078] In some embodiments,

number

[0079] In some embodiments, at least 50% of the oxidant is added to the leaching mixture after the contacting step, and optionally, at least 50% of the oxidant is added to the leaching mixture after the contacting step, where hydrogen gas is generated and the hydrogen gas generation rate has decreased to 10% of the maximum hydrogen gas generation rate during the contacting step.

[0080] In some embodiments, at least 50% of the oxidant is added to the leaching mixture after the contacting step, where hydrogen gas is generated and at least 50% of the oxidant is added to the leaching mixture after the hydrogen gas generation rate has decreased to 10% of the maximum hydrogen gas generation rate during the contacting step.

[0081] In some embodiments, at least 10% of the oxidant is added to the leaching mixture after the contacting step, and optionally, at least 10% of the oxidant is added to the leaching mixture after the contacting step, where hydrogen gas is generated and the hydrogen gas generation rate has decreased to 10% of the maximum hydrogen gas generation rate during the contacting step.

[0082] In some embodiments, at least 10% of the oxidant is added to the leaching mixture after the contacting step, where hydrogen gas is generated and at least 10% of the oxidant is added to the leaching mixture after the hydrogen gas generation rate has decreased to 10% of the maximum hydrogen gas generation rate during the contacting step.

[0083] In some embodiments, at least 90% of the oxidant is added to the leaching mixture after the contacting step, and optionally, at least 90% of the oxidant is added to the leaching mixture after the contacting step, where hydrogen gas is generated and the hydrogen gas generation rate has decreased to 10% of the maximum hydrogen gas generation rate during the contacting step.

[0084] In some embodiments, at least 90% of the oxidant is added to the leaching mixture after the contacting step, where hydrogen gas is generated and at least 90% of the oxidant is added to the leaching mixture after the hydrogen gas generation rate has decreased to 10% of the maximum hydrogen gas generation rate during the contacting step.

[0085] In some embodiments, the method further comprises adding an additional oxidant to the leaching mixture comprising at least one selected from O2, NO, hydrogen peroxide, and peroxodisulfate, optionally adding the additional oxidant to the leaching mixture after the contacting step, in which hydrogen gas is generated and the hydrogen gas generation rate has decreased to 10% of the maximum hydrogen gas generation rate during the contacting step.

[0086] In some embodiments, the method further includes adding an additional oxidant to the leaching mixture comprising at least one selected from O2, NO, hydrogen peroxide, and peroxodisulfate, wherein the additional oxidant is added to the leaching mixture after the contacting step, in which hydrogen gas is generated and the hydrogen gas generation rate has decreased to 10% of the maximum hydrogen gas generation rate during the contacting step.

[0087] In some embodiments, the method further includes adding a reducing agent to the leach mixture comprising at least one selected from SO, metabisulfite, bisulfite, dithionate, thiosulfate, H2O2, and H2, optionally adding the reducing agent after at least 50% of the copper has been oxidized.

[0088] In some embodiments, the method further includes adding a reducing agent to the leach mixture comprising at least one selected from SO, metabisulfite, bisulfite, dithionate, thiosulfate, H2O2, and H2, optionally adding the reducing agent after at least 10% of the copper has been oxidized.

[0089] In some embodiments, the method further includes adding a reducing agent to the leach mixture comprising at least one selected from SO, metabisulfite, bisulfite, dithionate, thiosulfate, H2O2, and H2, optionally adding the reducing agent after at least 90% of the copper has been oxidized.

[0090] In some embodiments, the acidic aqueous solution comprises at least one acid selected from H2SO4, methanesulfonic acid, and nitric acid.

[0091] In some embodiments, the acidic aqueous solution has an acid concentration in the range of 18 mol / L to 0.0001 mol / L. In some embodiments, the acidic aqueous solution has an acid concentration in the range of 18 mol / L to 0.001 mol / L. In some embodiments, the acidic aqueous solution has an acid concentration in the range of 18 mol / L to 0.01 mol / L. In some embodiments, the acidic aqueous solution has an acid concentration in the range of 18 mol / L to 0.1 mol / L. In some embodiments, the acidic aqueous solution has an acid concentration in the range of 18 mol / L to 1 mol / L. In some embodiments, the acidic aqueous solution has an acid concentration in the range of 10 mol / L to 0.0001 mol / L. In some embodiments, the acidic aqueous solution has an acid concentration in the range of 1 mol / L to 0.0001 mol / L. In some embodiments, the acidic aqueous solution has an acid concentration in the range of 10 mol / L to 1 mol / L.

[0092] In some embodiments, the method includes leaching a material by a method disclosed herein to obtain an aqueous solution containing metal ions, and separating the metal ions to obtain at least one essentially pure metal ion solution and / or at least one essentially pure solid metal ion salt.

[0093] In some embodiments, there is provided a method for recycling at least one battery material selected from lithium ion batteries, lithium ion battery waste, lithium ion battery manufacturing scrap, lithium ion cell manufacturing scrap, lithium ion active cathode materials, and combinations thereof, the method comprising: optionally heat treating the at least one battery material at a temperature in the range of 350° C. to 900° C.; mechanically crushing the at least one battery material to obtain a black mass; optionally classifying the black mass to obtain a fine fraction and a coarse fraction; and subjecting the black mass, and optionally the fine fraction, the coarse fraction, or the fine fraction and the coarse fraction, to a leaching method disclosed herein.

[0094] In some embodiments, there is provided a method for recycling at least one battery material selected from lithium ion batteries, lithium ion battery waste, lithium ion battery manufacturing scrap, lithium ion cell manufacturing scrap, lithium ion active cathode materials, and combinations thereof, the method comprising: heat treating the at least one battery material at a temperature in the range of 350° C. to 900° C.; mechanically crushing the at least one battery material to obtain black agglomerates; and subjecting the black agglomerates to a leaching method disclosed herein.

[0095] In some embodiments, there is provided a method for recycling at least one battery material selected from lithium ion batteries, lithium ion battery waste, lithium ion battery manufacturing scrap, lithium ion cell manufacturing scrap, lithium ion active cathode materials, and combinations thereof, the method comprising: optionally heat treating the at least one battery material at a temperature in the range of 350° C. to 900° C., mechanically crushing the at least one battery material to obtain black agglomerates, and subjecting the black agglomerates to a leaching method disclosed herein.

[0096] In some embodiments, the formula Li p M q M' r O s with a second material comprising copper in a zero oxidation state, the method comprising the steps of contacting the first material with an acidic aqueous solution having a pH of less than 6 to form a mixture; and reducing the first material with the second material, wherein M comprises one or more metals selected from nickel, manganese, and cobalt; M' comprises one or more metals selected from Mg, Ca, Ba, Al, Ti, Zr, Zn, Fe, V, Mo, and W; p is in the range of 1 to 1.4; q is in the range of 0.6 to 2; r is in the range of 0 to 1; s is in the range of 2 to 4; and the total amount of copper, expressed in moles, present in the second material prior to the reduction step divided by the total amount of the first material, expressed in moles;

number

number

number

[0097] In some embodiments, the black mass is slurried in water. The slurried black mass is in the range of 5% to 30% by weight percentage of the black mass by the total weight of the slurry. In some embodiments, the slurried black mass is contacted with an acidic aqueous solution having a pH of less than 6. In some embodiments, an acidic aqueous solution having a pH of less than 6 is formed from the slurried black mass by addition of an acid and an oxidizing agent. In some embodiments, the weight ratio of H2SO4 to black mass in the acidic aqueous solution ranges from 1:1 to 2:1. In some embodiments, H2SO4 is added during the contacting step to adjust the pH.

[0098] In some embodiments, the black mass is provided as a slurry. In some embodiments, the black mass is provided as a slurry in water. In some embodiments, the black mass is provided as a slurry in an aqueous sidestream from a subsequent processing step, such as a wash liquid from a filter. In some embodiments, the black mass is provided as a solid.

[0099] In some embodiments, the active cathode material is provided as a slurry. In some embodiments, the active cathode material is provided as a slurry in water. In some embodiments, the active cathode material is provided as a slurry in an aqueous side stream from a subsequent processing step, such as a wash liquid from a filter. In some embodiments, the active cathode material is provided as a solid.

[0100] In some embodiments, a method for leaching includes contacting the material with an acidic aqueous solution having a pH of less than 6, and then subsequently reducing one or more selected from metal oxides, metal hydroxides, and combinations thereof with a reducing agent.

[0101] In some embodiments, the acidic aqueous solution comprises at least one selected from H2SO4, O2, N2O, and combinations thereof. In some embodiments, the acidic aqueous solution comprises H2SO4. In some embodiments, the acidic aqueous solution comprises one or more acids selected from H2SO4, CH3SO3H, HNO3, and combinations thereof. In some embodiments, the acidic aqueous solution further comprises one or more selected from O2, N2O, and combinations thereof. In some embodiments, the only oxidizing agent added to the acidic aqueous solution is an oxidizing agent having the formula Li p M q M' r O s In some embodiments, the acidic aqueous solution includes an acid that is also an oxidizing agent, such as H2SO4. In some embodiments, the acidic aqueous solution includes an oxidizing agent that is not an acid, such as O2, N2O, or a combination thereof. In some embodiments, the acidic aqueous solution includes an acid and an oxidizing agent. In some embodiments, the acidic aqueous solution includes an acid and an oxidizing agent. p M q M' r O s In some embodiments, the acidic aqueous solution includes an acid that is also an oxidizing agent, and further includes an oxidizing agent that is not an acid.

[0102] In some embodiments, the reducing agent is one or more selected from SO2, metabisulfite, bisulfite, thiosulfate, dithionate, H2O2, H2, and combinations thereof.

[0103] In some embodiments, the method further comprises adjusting the pH of the aqueous solution with the mixed hydroxide precipitate. In some embodiments, the method further comprises adjusting the pH of the aqueous solution with at least one compound selected from a transition metal hydroxide, a transition metal carbonate. In some embodiments, the transition metal of the compound is already present in the black mass. In some embodiments, the transition metal hydroxide is a CAM precursor. In some embodiments, the transition metal hydroxide and / or transition metal carbonate is provided as a slurry. In some embodiments, the transition metal hydroxide and / or transition metal carbonate is provided as a slurry in water. In some embodiments, the transition metal hydroxide and / or transition metal carbonate is provided as a slurry in an aqueous side stream from a subsequent processing step, such as a wash liquid from a filter. In some embodiments, the transition metal hydroxide and / or transition metal carbonate is provided as a solid.

[0104] In some embodiments, contacting the material with the acidic aqueous solution is carried out at a temperature ranging from 50° C. to 110° C. In some embodiments, contacting the material with the acidic aqueous solution is carried out for a period ranging from 2 hours to 4 hours. In some embodiments, contacting the material with the acidic aqueous solution is carried out at a first temperature, and the oxidation step is carried out at a second temperature, and the second temperature is in the range of 100% to 20% of the first temperature.

[0105] In some embodiments, contacting the material with the acidic aqueous solution is performed at a temperature ranging from 50° C. to 110° C. In some embodiments, contacting the material with the acidic aqueous solution is performed for a period ranging from 2 hours to 4 hours. In some embodiments, contacting the material with the acidic aqueous solution is performed at a first temperature, the oxidation step is performed at a second temperature, and the second temperature is in the range of 100% to 20% of the first temperature, and the reduction step is performed at a third temperature, and the third temperature is in the range of 80% to 20% of the first temperature.

[0106] In some embodiments, the aqueous acid solution comprises air. In some embodiments, no oxygen-containing gas is sparged through the leaching mixture. In some embodiments, the aqueous acid solution does not comprise air. In some embodiments, the aqueous acid solution comprises less than 1000 ppm air. In some embodiments, the air comprises 3% or less by volume of sulfur dioxide. In some embodiments, contacting the material with an aqueous acid solution having a pH of less than 6 comprises sparging air through the aqueous acid solution. In some embodiments, air is sparged through the aqueous acid solution at a rate of 20% solution volume / min.

[0107] In some embodiments, the acidic aqueous solution has a pH in the range of -1.0 to 3.

[0108] In some embodiments, contacting the material with an acidic aqueous solution having a pH of less than 6 comprises first contacting the material with an acid to cause the formation of hydrogen gas, and, following the formation of hydrogen gas, adding an oxidizing agent. In some embodiments, contacting the material with an acidic aqueous solution having a pH of less than 6 comprises first contacting the material with an acid to cause the formation of hydrogen gas, monitoring the formation of hydrogen gas by gas chromatography and / or a hydrogen sensor, and, following the formation of hydrogen gas, adding an oxidizing agent. In some embodiments, contacting the material with an acidic aqueous solution having a pH of less than 6 comprises first contacting the material with an acid to cause the formation of hydrogen gas, monitoring the formation of hydrogen gas by gas chromatography and / or a hydrogen sensor, and, if the concentration of hydrogen gas is less than 5% by volume, such as less than 1% by volume, such as less than 0.1% by volume, adding an oxidizing agent.

[0109] In some embodiments, excess oxidizing gases O2, e.g., from air, and / or N2O are recycled from the exhaust gas back to the leaching reactor.

[0110] In some embodiments, the reducing agent comprises SO2, and the SO2 is sparged through the solution at a rate of 20% solution volume / min or less for 1 hour to 3 hours. In some embodiments, the reducing agent comprises SO2, and the SO2 is provided as a mixture with O2 or air containing 10% or more SO2. In some embodiments, the reducing agent comprises SO2, and the SO2 is not provided as a mixture with O2 or air. In some embodiments, the reducing agent comprises SO2, and the SO2 is provided as a pure gas having a purity of at least 90%, e.g., 99%, or as a mixture with an inert gas, e.g., nitrogen and / or argon.

[0111] In some embodiments, the reduction step is carried out at ambient temperature.

[0112] In some embodiments, following the contacting step, the method further comprises adding a base. In some embodiments, the base is selected from CaO, a hydroxide salt, a carbonate salt, and combinations thereof. In some embodiments, the hydroxide salt is selected from LiOH, NaOH, KOH, NH4OH, Ca(OH)2, CaCO3, Ni(OH)2, Co(OH)2, Mn(OH)2, and combinations thereof.

[0113] In some embodiments, the method is carried out batchwise.

[0114] In some embodiments, the method is carried out in at least two reaction vessels in series. In some embodiments, the method is carried out in, for example, three, four, five, six, seven, or more reaction vessels in series. In some embodiments, the black mass is added to a first reaction vessel, an oxidizing agent is added to a second and / or third reaction vessel, the cathode active material and / or mixed hydroxide precipitate is added to a fourth reaction vessel, and a reducing agent is added to a fourth, fifth, and / or sixth reaction vessel.

[0115] In some embodiments, excess sulfur dioxide is recycled from the exhaust gas back to the reactor.

[0116] In some embodiments, a reflux condenser is attached to at least one reaction vessel.

[0117] In some embodiments, contacting the material with the aqueous acidic solution is carried out at ambient pressure. In some embodiments, contacting the material with the aqueous acidic solution is carried out at elevated pressure.

[0118] In some embodiments, the contacting step is at a temperature ranging from 20° C. to 100° C. for a duration ranging from 10 minutes to 10 hours. In some embodiments, the contacting step is at 100° C. for a duration ranging from 3 hours to 5 hours. In some embodiments, the contacting step is at 60° C. for a duration ranging from 3 hours to 5 hours. In some embodiments, the contacting step is at 25° C. for a duration ranging from 3 hours to 5 hours.

[0119] In some embodiments, the oxidation step is at a temperature ranging from 20° C. to 100° C. for a duration ranging from 10 minutes to 10 hours. In some embodiments, the oxidation step is at 100° C. for a duration ranging from 3 hours to 5 hours. In some embodiments, the oxidation step is at 60° C. for a duration ranging from 3 hours to 5 hours. In some embodiments, the oxidation step is at 25° C. for a duration ranging from 3 hours to 5 hours.

[0120] In some embodiments, the reduction step is at a temperature ranging from 20° C. to 100° C. for a duration ranging from 10 minutes to 10 hours. In some embodiments, the reduction step is at 100° C. for a duration ranging from 3 hours to 5 hours. In some embodiments, the reduction step is at 60° C. for a duration ranging from 3 hours to 5 hours. In some embodiments, the reduction step is at 25° C. for a duration ranging from 3 hours to 5 hours.

[0121] In some embodiments, the method includes leaching a material disclosed herein to obtain an aqueous solution comprising metal ions, and separating the metal ions to obtain at least one essentially pure metal ion solution and / or at least one essentially pure solid metal ion salt.

[0122] In some embodiments, the essentially pure solid metal ion salt is a solid comprising a metal ion and a counterion, wherein the total mass of the metal ion and the counterion is at least 50% by weight of the solid, excluding the mass of the solvent, such as total water. In some embodiments, the essentially pure solid metal ion salt is a solid comprising a metal ion and a counterion, wherein the total mass of the metal ion and the counterion is at least 70% by weight of the solid, excluding the mass of the solvent. In some embodiments, the essentially pure solid metal ion salt is a solid comprising a metal ion and a counterion, wherein the total mass of the metal ion and the counterion is at least 80% by weight of the solid, excluding the mass of the solvent. In some embodiments, the essentially pure solid metal ion salt is a solid comprising a metal ion and a counterion, wherein the total mass of the metal ion and the counterion is at least 90% by weight of the solid, excluding the mass of the solvent. In some embodiments, the essentially pure solid metal ion salt is a solid comprising a metal ion and a counterion, wherein the total mass of the metal ion and the counterion is at least 95% by weight of the solid, excluding the mass of the solvent. In some embodiments, an essentially pure solid metal ion salt is a solid comprising a metal ion and a counterion, wherein the total mass of the metal ion and counterion is at least 99% by weight of the solid, excluding the mass of the solvent.

[0123] In some embodiments, the essentially pure metal ion solution is a solution comprising a metal ion, a counterion, and a solvent, where the total mass of the metal ion and the counterion is at least 50% by weight of the solution, excluding the weight of the solvent. In some embodiments, the essentially pure metal ion solution is a solution comprising a metal ion, a counterion, and a solvent, where the total mass of the metal ion and the counterion is at least 70% by weight of the solution, excluding the weight of the solvent. In some embodiments, the essentially pure metal ion solution is a solution comprising a metal ion, a counterion, and a solvent, where the total mass of the metal ion and the counterion is at least 80% by weight of the solution, excluding the weight of the solvent. In some embodiments, the essentially pure metal ion solution is a solution comprising a metal ion, a counterion, and a solvent, where the total mass of the metal ion and the counterion is at least 90% by weight of the solution, excluding the weight of the solvent. In some embodiments, the essentially pure metal ion solution is a solution comprising a metal ion, a counterion, and a solvent, where the total mass of the metal ion and the counterion is at least 95% by weight of the solution, excluding the weight of the solvent. In some embodiments, an essentially pure metal ion solution is a solution comprising a metal ion, a counterion, and a solvent, wherein the total mass of the metal ion and counterion, excluding the mass of the solvent, is at least 99% by weight of the solution.

[0124] In some embodiments, separating the metal ions to obtain at least one essentially pure metal ion solution and / or at least one essentially pure solid metal ion salt comprises one or more of solid / liquid separation, extraction, precipitation, crystallization, and combinations thereof.

[0125] In some embodiments, the method may be implemented in part or in whole as a continuous process controlled by sensors and actuators and as part of a computer-based process control system.

[0126] Electron equivalent: Without wishing to be bound by theory, it is believed that during the leaching process, electrons are transferred from a metal in the zero oxidation state, such as copper, to a metal of the formula Li p Mq M' r O s In addition, for example, copper is converted to an oxidant of the formula Li p M q M' r O s The oxidizing agent represented by the formula Li p M q M' r O s The number of electrons per mole of oxidant, expressed as:

number

number

[0127] Average oxidation number of M'

number

[0128] For example, Li (1+x) (Ni a Co b Mn cM ’ d ) (1-x) O2 (x=0.1, a=b=c=0.3 and d=0.1, and M' is Zr in the +4 oxidation state) is Li p M q M' r O s (p=1.1, q=0.81, r=0.09 and s=2), and n(e M ) = 1.14 (Here and in the following examples, n(e M ) is rounded to two decimal places).

[0129] For example, Li (1+x) (Ni a Co b Mn c M ’ d ) (1-x) O2 (x=0.1, a=b=c=0.3 and d=0.1, and M' consists of 30 mol% Mg, 20 mol% Zr, 10 mol% V and 40 mol% W, with the average oxidation number Ox M’ = 0.3 × 2 + 0.2 × 4 + 0.1 × 5 + 0.4 × 6 = 4.3) is Li p M q M' r O s (p=1.1, q=0.81 r=0.09 and s=2), and (e M )=1.10.

[0130] For example, Li[Ni h Co i Al j ]O 2+t (h=0.9, i=0.1, j=0.05 and t=0.2) is Li p M q M' r O s (p=1.1, q=1, r=0.05 and s=2.2), where n(e M )=1.25.

[0131] For example, Li (1+x) Mn 2-x-y-z My M ’ z O4 (x=0.2, y=z=0.05, and M' is Mg in oxidation state +2) is Li p M q M' r O s (p=1.2, q=1.75, r=0.05 and s=4), where n(e M )=1.83.

[0132] For example, xLi (1+1 / 3) M (2 / 3) O2·yLiMO2·zLiM'O2 (x=0.9, y=z=0.05 and M' is W with oxidation state +6) is Li p M q M' r O s (p=1.3, q=0.65, r=0.05 and s=2), where n(e M )=1.69.

[0133] Example batch process: FIG. 1 illustrates an exemplary batch process (100) consistent with some embodiments of the present disclosure. In some embodiments, a material (102), such as a black mass containing copper, is acid leached in a continuous stirred reaction vessel (101) containing an aqueous acidic solution at a pH below 0. In some embodiments, hydrogen gas is evolved (105). In some embodiments, a solution of formula Li p M q M' r O s An oxidizing agent represented by the formula: is added (103). In some embodiments, the pH is adjusted to a pH in the range of 1-2, for example using a mixed hydroxide precipitate, and a reducing agent, for example SO2, is introduced (104). In some embodiments, the resulting liquid phase (106) and solid phase (105) are separated by solid-liquid separation, for example by filtration, centrifugation, and / or sedimentation.

[0134] Exemplary continuous processes: FIG. 2 illustrates an exemplary continuous process (200) consistent with some embodiments of the present disclosure. In some embodiments, a material (202), such as a black mass containing copper, is acid leached in a continuous stirred reaction vessel (201) containing an aqueous acidic solution at a pH less than 0. In some embodiments, the acid leaching is further carried out in one or more additional continuous stirred reaction vessels (203). In some embodiments, a copper-containing black mass is acid leached in a continuous stirred reaction vessel (204) containing an aqueous acidic solution at a pH less than 0. In some embodiments, a copper-containing black mass is acid leached in a continuous stirred reaction vessel (205) containing an aqueous acidic solution at a pH less than 0. In some embodiments, a copper-containing black mass is acid leached in a continuous stirred reaction vessel (206) containing an aqueous acidic solution of formula Li p M q M' r O s An oxidizing agent represented by the formula: is added (205) to the continuous stirred reaction vessel (204). In some embodiments, further acid leaching in the presence of the added oxidizing agent is carried out in one or more additional continuously stirred reaction vessels (206). In some embodiments, the pH is adjusted to a pH in the range of 1-2, for example using a mixed hydroxide precipitate, and a reducing agent, for example SO2, is introduced (208) to the continuous stirred reaction vessel (207). In some embodiments, further leaching in the presence of the added reducing agent is carried out in one or more additional continuously stirred reaction vessels (209). In some embodiments, the resulting liquid phase (211) and solid phase (210) are separated by solid-liquid separation, for example by filtration, centrifugation, and / or settling. EXAMPLES

[0135] The following examples are intended to be illustrative and not limiting of the scope of the disclosure in any way.

[0136] Abbreviation % Percent K2CO3 Potassium Carbonate Na2CO3 Sodium Carbonate Na2B4O7 Sodium Tetraborate PA grade Professional analysis grade nd Not decided wt% Mass percent NaOH Sodium hydroxide Li Lithium Ni Nickel Co Cobalt Mn Manganese Cu Copper Al Aluminum Fe Iron P. Lin F Fluorine Ca Calcium

[0137] Exemplary elemental analysis Elemental analysis of the solid samples was performed by digestion with nitric acid and hydrochloric acid (feed sample, examples 1 and 2) or by digestion by K2CO3-Na2CO3 / Na2B4O7 fusion and dissolution of the fusion residue in hydrochloric acid (examples 3 and 4).

[0138] Metals in the obtained sample solutions were measured by optical emission spectroscopy using inductively coupled plasma (ICP-OES).

[0139] Regarding the sample preparation for the overall fluorine content determination (waste samples), elemental analysis of fluorine and fluoride was carried out according to DIN EN 14582:2016-12; detection method was ion-selective electrode measurement; DIN 38405-D4-2:1985-07 (water samples; digestion of inorganic solids followed by acid-assisted distillation and determination of fluoride with an ion-selective electrode).

[0140] Total carbon was measured by gas chromatography using a thermal conductivity detector on the gas obtained after combustion of the samples.

[0141] Sulfur was determined by catalytic combustion of the samples in an inert gas / oxygen atmosphere, where it is converted to a mixture of SO2 and SO3. The SO3 formed was reduced to SO2 with copper granules. After drying and separation of the combustion gases, sulfur was detected and quantified as SO2 by thermal conductivity or IR spectroscopy.

[0142] Black lump For the examples presented below, the black mass was obtained by a process involving the pyrolysis of battery scrap. The material contained small amounts of sulfur. The analyzed metals were present as oxidizing compounds such as MnO, CoO, NiO, salts such as LiF, LiAlO2, Li2CO3, and / or metals in the zero oxidation state such as nickel, cobalt, and copper. The carbon was primarily elemental carbon in the form of graphite or coke with some soot.

[0143] The compositions of the black lump 1 used in Examples 1 to 4 and the black lump 2 used in Examples 5 to 7 are shown in Table 1.

[0144] [Table 1]

[0145] Figure 3 shows the XRD pattern of the black mass 1. In Figure 3, "a" represents graphite, "b" represents nickel-cobalt-manganese, "c" represents NiO, "d" represents CoO, "e" represents MnO, "f" represents Ni, and the remaining reflections correspond to lithium salts and impurities.

[0146] Formula Li p M q M' r O s Positive electrode active material represented by The positive electrode active material (CAM) used in the examples was a NCM111 type material containing approximately equimolar amounts of nickel, cobalt, and manganese. The composition of this material was Li (x+1) (Ni 0,34 Co 0,32 Mn 0,34 ) (1-x) O2(x=0.0628). This material is Li p M q M' r O s can also be written as, p = 1.0682, q = 0.9372, r = 0, s = 2, and n(e M)=1.13. The formal average oxidation state of nickel, cobalt, and manganese is +3.1340, i.e., 13.4% of nickel, cobalt, and manganese are in the oxidation state +4, and 86.6% are in the oxidation state +3. The composition of the CAM was 19.8% by weight Ni, 18.9% by weight Co, 18.3% by weight Mn, and 7.8% by weight Li.

[0147] Example 1 In this example, the black mass was contacted with an acidic aqueous solution having a pH of less than 6, and air was added as an oxidizing agent, and the resulting solution had the formula Li p M q M' r O s No oxidizing agent represented by the formula (I) was added. Then, the reducing agent SO2 was added.

[0148] In a reaction vessel, 162.37 g of black mass 1 was suspended in 348.65 g of deionized water under an argon atmosphere. The reaction vessel was kept constant under an argon flow of 20 normal liters per hour. To this mixture, 227.32 g of sulfuric acid (96 w%) was slowly added over a period of about 45 minutes under stirring at 500 rpm with a Rushton turbine. The added acid corresponded to a calculated initial acid concentration (w / o reaction) of 39.5% and an acid to black mass mass ratio of 1.4. After the acid addition, the reactor was heated to 100°C in about 115 minutes. Hydrogen was evolved and the redox potential of the solution was about -140 mV vs. Ag / AgCl2. Hydrogen evolution was measured by an on-line gas chromatograph. Hydrogen evolution stopped 152 minutes after the start of sulfuric acid addition, during which a total of 8.2 normal liters of H2 was evolved. This corresponded to 0.37 moles of hydrogen. After this, the reactor temperature decreased and reached 80 °C after 30 min, and the redox potential was observed to decrease to -180 mV. A sample of the reactor slurry was filtered and analyzed by X-ray fluorescence analysis. The filtrate contained 2.02% Ni, 1.296% Co, 1.367% Mn, and 0.003% Cu.

[0149] The gas supply was then changed from argon to 20 normal liters per hour of air and the stirring speed was increased to 1200 rpm to ensure good gas-liquid mixing. Within 30 minutes the redox potential had risen to +83 mV and after another 90 minutes it had reached +131 mV. Another sample was then taken from the reactor, filtered and analyzed by X-ray fluorescence analysis. The filtrate was found to contain 2.024% Ni, 1.283% Co, 1.348% Mn and 0.139% Cu. Without wishing to be bound by theory, it is believed that the increase in the redox potential due to the addition of air significantly increased the rate of copper dissolution.

[0150] The reaction gas was then changed from air to sulfur dioxide. After another 120 min under sulfur dioxide atmosphere, the reaction mixture was cooled to room temperature and filtered. The filter residue was washed and dried to obtain 49.1 g of dry material. The composition and corresponding elemental recoveries are shown in Table 2.

[0151] [Table 2]

[0152] Example 2 In this example, the black mass is contacted with an acidic aqueous solution having a pH of less than 6, with the addition of air as an oxidizing agent, and reacted with a compound of the formula Li p M q M' r O s , where the formula Li (x+1) (Ni 0,34 Co 0,32 Mn 0,34 ) (1-x) The oxidizing agent CAM, O2 (x=0.0628), was added, followed by the reducing agent SO2.

[0153] In a reaction vessel, 174.13 g of black mass 1 was suspended in 337.21 g of deionized water under an argon atmosphere. The reaction vessel was kept constant under an argon flow of 20 normal liters per hour. To this mixture, 243.78 g of sulfuric acid (96 w%) was slowly added over a period of about 55 minutes under stirring at 500 rpm with a Rushton turbine. The added acid corresponded to a calculated initial acid concentration (w / o reaction) of 42.0%, an acid to black mass mass ratio and a CAM ratio of 1.35. After the acid addition, the reactor was heated to 100°C in about 110 minutes. Hydrogen was evolved and the redox potential of the solution was about -180 mV vs. Ag / AgCl2. Hydrogen evolution was measured by an on-line gas chromatograph. Hydrogen evolution stopped 110 minutes after the start of sulfuric acid addition, during which a total of 7.7 normal liters of H2 was evolved. This was equivalent to 0.34 moles of hydrogen. After this the reactor temperature was decreased to reach 80°C after 30 minutes. A sample of the reactor slurry was taken, filtered and analyzed by X-ray fluorescence. The filtrate contained 1.514% Ni, 0.941% Co, 1.838% Mn and 0.004% Cu.

[0154] The gas supply was then changed from argon to 20 normal liters / hour of air and the stirring speed was increased to 1200 rpm to ensure good gas-liquid mixing. Within 30 minutes the redox potential had risen to +114 mV. At this point, 6.2 g of CAM was added as a dry powder to the reaction mixture. After stirring for an additional 90 minutes, another sample was taken from the reactor, filtered and analyzed by X-ray fluorescence analysis. The filtrate was determined to contain 1.497% Ni, 0.888% Co, 1.615% Mn and 0.546% Cu.

[0155] The reaction gas was then changed from air to sulfur dioxide (flow rate of about 3 g / h). After another 80 min under sulfur dioxide atmosphere, corresponding to a total feed of about 4 g SO2, the reaction mixture was cooled to room temperature and filtered. The filter residue was washed and dried to obtain 42.0 g of dry material. The composition and corresponding elemental recoveries are shown in Table 3.

[0156] [Table 3]

[0157] Comparing Example 1 and Example 2, Example 2 shows that under similar reaction conditions, the addition of CAM increased the copper recovery from 55% to 99%. Without wishing to be bound by theory, Example 2 shows that 0.23 equivalents of electrons (Cu→Cu+2e - ) corresponds to 0.115 moles of Cu, and 0.066 moles of CAM (i.e.

number

[0158] Example 3 In this example, the black mass is contacted with an acidic aqueous solution having a pH of less than 6, without the addition of air, and the compound is dissolved in water of formula Li p M q M' r O s The oxidizing agent represented by the formula Li (x+1) (Ni 0,34 Co 0,32 Mn 0,34 ) (1-x) The CAM of O2 (x=0.0628) was added, followed by the addition of the reducing agent SO2.

[0159] In a reactor, 139.6 g of black mass 1 was suspended in 357.7 g of deionized water under an argon atmosphere. The reactor was kept constant under an argon flow of 20 normal liters per hour. To this mixture, 208 g of sulfuric acid (96 wt%) was slowly added over a period of about 18 minutes under stirring at 500 rpm with a Rushton turbine. The added acid corresponded to a calculated initial acid concentration (w / o reaction) of 35.3%, an acid to black mass mass ratio and a CAM ratio of 1.34. After the acid addition, the reactor was heated to 100°C within about 56 minutes. Hydrogen was evolved and the redox potential of the solution was about -130 mV vs. Ag / AgCl2. 110 minutes after the start of the sulfuric acid addition, hydrogen evolution ceased. A sample of the reactor slurry was taken, filtered and analyzed by X-ray fluorescence analysis. The filtrate contained 1.909% Ni, 1.224% Co, 1.296% Mn, and 0.007% Cu.

[0160] After an additional 11 minutes, 9 g of CAM was added as a dry powder to the reaction mixture. After stirring for an additional 30 minutes during which the reactor temperature was cooled to 80°C, another sample was taken from the reactor, filtered, and analyzed by X-ray fluorescence analysis. The filtrate was determined to contain 2,028% Ni, 1.349% Co, 1.416% Mn, and 0.314% Cu, and had a pH value of 0.04.

[0161] The reactor was held at 80°C under nitrogen for an additional hour, during which time there was no significant change in the metal content in solution, and then the reactor was cooled to ambient temperature and left under nitrogen overnight.

[0162] The next day the reactor was heated to 80°C. The metal concentrations in solution had increased slightly to 2.149% Ni, 1.436% Co, 1.524% Mn and 0.364% Cu. 67 minutes after reaching 80°C the nitrogen flow was stopped and replaced with a pure sulfur dioxide gas flow of 2.2 g / h. The Rushton turbine agitator speed was increased to 1200 rpm. The reactor was held at these conditions for a further 120 minutes, corresponding to a total SO2 feed of 4.4 g.

[0163] The sulfur dioxide was then replaced with nitrogen, the stirrer speed was reduced to 500 min-1, and the reactor heat was turned off. When the reactor contents reached room temperature, they were filtered, and the filter cake was washed and dried. The final filter cake mass was 41.1 g (corrected for sample mass). The final composition of the filter cake and the corresponding metal recoveries in the leachate are summarized in Table 4.

[0164] [Table 4]

[0165] Without wishing to be bound by theory, in Example 3, 0.184 equivalents of electrons (Cu→Cu+2e - ) corresponds to 0.092 moles of Cu, and 0.096 moles of CAM (i.e.

number

[0166] Example 4 In Example 4, the procedure of Example 3 was repeated, except that the amount of sulfuric acid was reduced and the amount of SO2 fed was increased.

[0167] Thus, 139.6 g of black mass 1 was suspended in 386.0 g of deionized water under an argon atmosphere. The reaction vessel was kept constant under an argon flow of 20 normal liters per hour. To this mixture, 175 g of sulfuric acid (96 wt%) was slowly added over a period of about 20 minutes under stirring at 500 rpm with a Rushton turbine. The added acid corresponded to a calculated initial acid concentration (w / o reaction) of 30.0%, an acid to black mass mass ratio and a CAM ratio of 1.13. A sample of the liquid phase was analyzed 38 minutes after the addition of 9 g of CAM. This liquid phase contained 2.105% Ni, 1.411% Co, 1.48% Mn and 0.235% Cu, with a pH value of 0.7. 102 min after CAM addition, SO2 was fed to the reactor at 80°C at a rate of 4.3 g / h, which corresponded to feeding 8.6 g SO2 in 120 min. The final metal recovery results are summarized in Table 5. The mass of the dried filter residue was 41.2 g.

[0168] [Table 5]

[0169] Without wishing to be bound by theory, 0.184 equivalents of electrons (Cu → Cu + 2e - ) corresponds to 0.092 moles of Cu, and 0.096 moles of CAM (0.109 equivalents of electrons (Li (1+x) M (1-x) O2+(1+x) / (1-x)e - →Li2O+MO) in the absence of air. Comparing Example 3 and Example 4, the effect of acid concentration on the oxidation of copper by CAM was observed.

[0170] Example 5 In this example, the black mass is contacted with an acidic aqueous solution having a pH of less than 6, without the addition of air, and is reacted with an acid of formula Li p M q M' r O s The oxidizing agent represented by the formula Li (x+1) (Ni 0,34 Co 0,32 Mn 0,34) (1-x) CAM represented by O2 (x=0.0628) was added. After that, no reducing agent (SO2) was added.

[0171] In a reaction vessel equipped with a reflux condenser and a dropping funnel, 1209.2 g of black mass 2 was suspended in 2883.1 g of deionized water under nitrogen atmosphere. The reaction vessel was flushed with nitrogen and kept under a constant flow of 20 normal liters per hour of nitrogen throughout the experiment. To this mixture, 1538.5 g of sulfuric acid (96 w%) was slowly added over a period of about 270 minutes at an initial temperature of 40° C. while stirring at 500 rpm using a triple cross beam stirrer. During this period, the temperature in the reactor was kept between 50° C. and 60° C. Hydrogen gas was evolved and some bubbling occurred in the reaction mixture. For this reason, the acid addition and heating were carried out slowly. After the acid addition, the temperature was kept at 50° C. for a further 185 minutes, after which the reactor was cooled and kept at room temperature overnight for a further 855 minutes. The reaction mixture was then heated to 62° C. for a further 113 minutes, and then another 225 g of sulfuric acid (96%) was added over 55 minutes. The total acid added corresponded to a calculated initial acid concentration of 36.4% (w / o reaction) and an acid to black mass ratio of 1.3. After completion of acid addition, the reactor was heated to 100°C within 169 minutes. The reactor contents were held at this temperature for an additional 53 minutes before the first sample was taken, filtered, and the washed filter residue was analyzed by X-ray fluorescence analysis as a wet filter cake. The filter residue contained 0.69% Ni, 0.1% Co, 0.01% Mn, and 2.13% Cu. The moisture content of the filter residue was approximately 50%, indicating that most of the copper was likely not dissolved.

[0172] When hydrogen gas evolution had ceased, the reactor was cooled to 80°C. 66 min after the first sample was taken, 80 g of pure CAM was added as a dry powder to the reaction mixture. 30 min after the addition of CAM, a second sample was taken, filtered, and the washed wet filter residue was analyzed by X-ray fluorescence analysis. The residue contained 0.56% Ni, 0.09% Co, 0.01% Mn, and the Cu content was 0.618%.

[0173] An additional 8 g of CAM was added and another sample was taken after another 31 minutes. The Cu content of the washed wet filter residue had dropped to 0.56% and the sample contained 0.54% Ni, 0.08% Co and 0.01% Mn. Meanwhile the temperature of the reactor had reached 80°C. An additional 15 g of CAM was added and another sample was taken after another 30 minutes. The Cu content of the washed wet filter residue had only slightly dropped to 0.54%. The reactor was held at 80°C for an additional 21 minutes, after which the reactor was cooled and held at room temperature overnight for an additional 882 minutes.

[0174] The reactor was then reheated to 80°C for a further 70 min. A fifth sample was taken to check the progress of the reaction overnight. The Cu content of the washed wet filter cake was 0.47% and the pH value of the filtrate was 1.3. 40 min after the fifth sample, 100 g of sulfuric acid (96%) was added to increase the acidity of the reaction mixture. After a further 35 min, a sixth sample was taken and the washed wet filter cake contained 0.37% Ni, 0.05% Co, 0.009% Mn and 0.34% Cu. After a further 63 min, 11.5 g of CAM was added. After a further 93 min, another 11.5 g of CAM was added to the reactor.

[0175] Samples were taken 40 min after each addition and the washed wet filter cakes were analyzed to contain Cu at 0.29% and 0.11%, respectively.

[0176] A ninth and final sample was taken 81 minutes after the latter sampling and the washed wet filter cake was analysed: the residue contained 0.26% Ni, 0.04% Co, 0.01% Mn and 0.13% Cu.

[0177] At this point, 1202 g of deionized water was added. The reactor was cooled to room temperature and held at room temperature overnight. The reactor contents were then filtered and the filter cake was washed with four aliquots of deionized water totaling 3.906 g. The wet filter cake had a mass of 847.5 g and a moisture content of 43.7%. The recovered filtrate had a mass of 5751 g. The total wash filtrate mass was 5182 g. The elemental composition of the filter cake and the calculated leach recovery are summarized in Table 6.

[0178] [Table 6]

[0179] Without wishing to be bound by theory, it is believed that 1.56 equivalents of electrons (Cu → Cu + 2e - ) corresponds to 0.78 moles of Cu, which is converted to 1.35 moles of CAM (1.53 equivalents of electrons (Li (1+x) M (1-x) O2+(1+x)H + +(1+x) / (1-x)e - →(1+x) / 2Li2O+(1-x)MO+(1+x) / 2H2O) is considered to be oxidized without air. The ratio (mol Cu) / (mol CAM) is 0.58, and n(e M ) 0.51 was obtained.

[0180] Example 6 In this example, the black mass is contacted with an acidic aqueous solution having a pH of less than 6, no air is added, and the solution is treated with a solution of formula Li p M q M' r O s The oxidizing agent represented by the formula Li (x+1) (Ni 0,34 Co 0,32 Mn 0,34 ) (1-x) CAM expressed as O2 (x=0.0628) was added before the start of sulfuric acid injection. No reducing agent (SO2) was added thereafter.

[0181] In a reaction vessel equipped with a reflux condenser and a dropping funnel, 909.1 g of black mass 2 and 94.7 g of CAM were suspended in 2166 g of deionized water under a nitrogen atmosphere. The amount of CAM added at the beginning of the reaction corresponds to the stoichiometrically calculated amount required for the dissolution of copper contained in the reaction mixture. The reaction vessel was flushed with nitrogen and kept under a constant flow of 20 normal liters per hour of nitrogen throughout the experiment.

[0182] The reactor contents were heated to 80°C and then 1321 g of sulfuric acid (96 w%) was slowly added at the starting temperature over a period of approximately 250 minutes while stirring at 500 rpm using a triple cross beam stirrer. The reactor temperature was maintained at 80°C during this period. Hydrogen gas was evolved and some bubbling occurred in the reaction mixture. For this reason, the acid addition was performed slowly. After the acid addition, the temperature was held at 80°C for 25 minutes and then increased to 99°C within 100 minutes. The reactor temperature was held at 99°C for an additional 90 minutes. An initial sample was taken and analyzed, which showed that the wet filter residue contained 0.6% Ni, 0.08% Co, 0.006% Mn and 1.32% Cu, and the filtrate contained 5.3% Ni, 2.1% Co, 0.5% Mn and 0.04% Cu. These data indicate that most of the Ni, Co, and Mn in the black mass have already dissolved, and only a small amount of copper has been leached out.

[0183] The reactor was then cooled and held at room temperature overnight for 925 minutes. The reaction mixture was then heated to 80°C for an additional 72 minutes and 182 g water and 100 g sulfuric acid (96%) were added in 9 minutes. After 13 minutes, 66.5 g CAM was added to the reactor. After 52 minutes, a second sample was taken and analyzed, the wet filter residue contained 0.44% Ni, 0.06% Co, 0.007% Mn and 0.64% Cu. 23 minutes after the second sample, an additional 28.4 g CAM was added to the reactor.

[0184] After a further hour a third sample was taken and analysed: the wet filter residue contained 0.43% Ni, 0.06% Co, 0.01% Mn and 0.25% Cu, and the filtrate contained 5.2% Ni, 2.3% Co, 0.8% Mn and 0.7% Cu.

[0185] Twenty-five minutes after the third sample was taken, an additional 30 g of sulfuric acid (96%) was added and the reactor contents were stirred for an additional 40 minutes. The added acid corresponded to a total calculated initial acid concentration of 36.6% (w / o reaction) and an acid to black mass mass ratio of 1.3.

[0186] After this time, the reactor was turned off and 876 g of deionized water was added to prevent crystallization of the metal salts upon cooling to room temperature. The slurry was then filtered to obtain 4338 g of filtrate. 847 g of water was poured into the reactor and this was also filtered, and five more portions of the filter residue wash filtrate were added and combined (total 5318 g). The wet filter cake weighed 682 g and had a moisture content of 42.0%. The elemental composition of the filter residue and calculated leach recoveries are summarized in Table 7.

[0187] [Table 7]

[0188] Without wishing to be bound by theory, in Example 6, 1.17 equivalents of electrons (Cu→Cu+2e - ) was converted to a total of 2.03 moles of CAM (2.30 equivalents of electrons (Li (1+x) M (1-x) O2+(1+x)H + +(1+x) / (1-x)e - →(1+x) / 2Li2O+(1-x)MO+(1+x) / 2H2O) is considered to be oxidized without air. The ratio (mol Cu) / (mol CAM) is 0.29, and n(e MA comparison of Examples 5 and 6 demonstrates the beneficial effect of adding CAM after hydrogen evolution has ceased (Example 5). In contrast, adding CAM at the beginning of the reaction (Example 6) may reduce the efficiency of copper oxidation by CAM due to partial reduction of CAM by evolved hydrogen.

[0189] Example 7 In this example, the black mass is contacted with an acidic aqueous solution having a pH of less than 6, no air is added, and the solution is treated with a solution of formula Li p M q M' r O s The oxidizing agent represented by the formula Li (x+1) (Ni 0,34 Co 0,32 Mn 0,34 ) (1-x) CAM expressed as O2 (x=0.0628) was added. The addition of sulfuric acid was performed while carefully controlling the pH value of the leachate to maintain a pH value of about 1.5 throughout the reaction. No reducing agent (SO2) was added thereafter.

[0190] In a reaction vessel equipped with a reflux condenser and a dropping funnel, 910.8 g of black mass 2 was suspended in 2166 g of deionized water under nitrogen atmosphere. The reaction vessel was flushed with nitrogen and kept under a constant flow of 20 normal liters per hour of nitrogen throughout the experiment. The reactor contents were heated to 80° C. within 86 minutes. 312 g of sulfuric acid (96 w%) was slowly added to this mixture at an initial temperature of 25° C. while stirring at 500 rpm using a triple cross beam stirrer within 30 minutes, lowering the pH value of the slurry from 12.3 to 2.1.

[0191] During this period, the reactor temperature was increased from 80°C to 92°C. Hydrogen gas was evolved and some bubbling occurred in the reaction mixture. The sulfuric acid addition was continued for the next 359 minutes while controlling to maintain the pH value at about 1.5. 100 minutes after the start of the acid addition, the reactor temperature began to increase and reached about 100°C 280 minutes after the start of the acid addition. At 409 minutes after the start of the acid addition, an additional 31 g of water was added to the reaction mixture. After 15 minutes, the first sample was taken, filtered, and analyzed. The wet filter residue contained 2.24% Ni, 0.36% Co, 0.007% Mn, and 1.72% Cu, and the filtrate contained 4.7% Ni, 1.6% Co, 0.08% Mn, and 0.01% Cu.

[0192] The reactor was then cooled and held overnight at room temperature for 885 minutes. The next day, the reactor was reheated to 100°C within 108 minutes. After 195 minutes, a second sample was taken and analyzed. The wet filter residue contained 0.79% Ni, 0.15% Co, 0.006% Mn, 1.77% Cu, and the filtrate contained 5.7% Ni, 1.8% Co, 0.09% Mn and 0.01% Cu. These data demonstrate that nickel, cobalt and manganese species were significantly leached at pH values ​​of about 1.5 during the pure acid leaching stage, while copper was barely dissolved.

[0193] After the second sampling, the reactor temperature was set to 90°C which was reached after 67 minutes. 82 minutes after the second sampling, 20.5g CAM and 11g water were added. 30 minutes after the first CAM addition, a third sample was taken, but analysis showed only a slight change. Therefore, 55 minutes after the first CAM addition, a further 21g CAM was added. After 38 minutes, a fourth sample was taken and analyzed. There was still a slight change in concentration, but the Cu concentration in the filtrate had increased to 0.2%.

[0194] The reactor was held at 90°C for an additional 32 minutes, then cooled and held at room temperature overnight for 930 minutes. The reactor was then heated again to 90°C within 105 minutes and 20.4 g of CAM was added. After 40 minutes, a fifth sample was taken and analyzed, showing that the wet filter residue contained 0.65% Ni, 0.09% Co, 0.02% Mn and 1.62% Cu, and the filtrate contained 5.8% Ni, 1.6% Co, 0.3% Mn and 0.3% Cu. Four more 50 g CAMs were added within 265 minutes, along with one aliquot of 11 g water. Another sample was taken 30 min after the last CAM addition and analyzed, the wet filter residue contained 0.41% Ni, 0.06% Co, 0.01% Mn and 0.26% Cu, the filtrate contained 5.2% Ni, 2.0% Co, 0.4% Mn and 0.6% Cu, and the pH value of the filtrate was 1.7. 50 min after the last sampling, the reactor was turned off and 851 g of deionized water was added so that the metal salts did not crystallize upon cooling to room temperature. The slurry was then filtered to obtain 3602 g of filtrate. 1003 g of water was flushed through the reactor and this was also filtered, and five more wash filtrates of the filter residue were added and combined (total 4814 g). The wet filter cake weighed 640 g and had a moisture content of 42.3%. The elemental composition of the filter residue and the calculated leaching recoveries are summarized in Table 8.

[0195] [Table 8]

[0196] Without wishing to be bound by theory, in Example 7, 1.18 equivalents of electrons (Cu→Cu+2e - 0.59 moles of Cu, equivalent to 1.2 moles of CAM (1.36 equivalents of electrons (Li (1+x) M (1-x) O2+(1+x)H + +(1+x) / (1-x)e -→(1+x) / 2Li2O+(1-x)MO+(1+x) / 2H2O) in the absence of air. The ratio (mol Cu) / (mol CAM) was 0.49, giving an n(eM) of 0.43.

Claims

1. 1. A method for leaching a material containing zero oxidation state copper, comprising: contacting the material with an acidic aqueous solution having a pH of less than 6 to form a leach mixture; Copper is dissolved in water with the formula Li p M q M' r O s and a step of oxidizing the mixture with an oxidizing agent represented by the formula: During the ceremony, M comprises one or more metals selected from nickel, manganese, and cobalt; M' comprises one or more metals selected from Mg, Ca, Ba, Al, Ti, Zr, Zn, Fe, V, Mo, and W; p is in the range of 1 to 1.4; q is in the range of 0.6 to 2; r ranges from 0 to 1; s ranges from 2 to 4, and The total amount of copper in moles present in the material before leaching was divided by the total amount of oxidizing agent in moles. [0010] is in the range [0025] and [0030] is the average oxidation number of M' determined by calculating the molar average of the most stable oxidation number of each metal as an oxide contained in M'. 【Request 2】 【Number 4】 The method of claim 1 , wherein the range is

3. The oxidizing agent is of the formula Li (1+x) (Ni a Co b Mn c M ’ d ) (1-x) O 2 The lithium nickel cobalt manganese oxide is represented by the formula: M ’ is selected from Mg, Ca, Ba, Al, Ti, Zr, Zn, Mo, V and Fe; zero≦x≦0.2, 0.1≦a≦0.95, zero≦b≦0.9, or 0.05<b≦0.5; zero≦c≦0.6, Zero≦d≦0.1, and 3. The method of claim 1 or 2, wherein a+b+c+d=1.

4. The oxidizing agent has the formula Li[Ni h Co i A j ]O 2+t The lithium nickel-cobalt aluminum oxide is represented by the formula: h is in the range of 0.8 to 0.95; i is in the range of 0.1 to 0.3; j ranges from 0.01 to 0.10, and The method according to claim 1 or 2, wherein t is in the range of 0 to 0.

4.

5. The oxidizing agent is of the formula Li (1+x) Mn 2-x-y-z M y M ’ z O 4 The lithium manganese oxide is represented by the formula: x ranges from zero to 0.2; y+z ranges from zero to 0.1, and M ’ The method according to claim 1 or 2, wherein is selected from Al, Mg, Fe, Ti, V, Zr and Zn.

6. The oxidizing agent is of the formula xLi (1+1/3) M (2/3) O 2 ・yLiMO 2 ・zLiM'O 2 wherein M comprises at least one metal in the oxidation state +4, M′ is at least one transition metal, and 0<x<1, 0<y<1, 0<z<1, and x+y+z=1.

7. 3. The method of claim 1 or 2, wherein the material is black agglomerate from a lithium ion battery material and the oxidant is a positive electrode active material.

8. 3. The method of claim 1 or 2, wherein at least 50% of the oxidant is added to the leach mixture after the contacting step, and optionally, wherein at least 50% of the oxidant is added to the leach mixture after the contacting step, where hydrogen gas is generated and the hydrogen gas generation rate has decreased to 10% of the maximum hydrogen gas generation rate during the contacting step.

9. The method of claim 7, wherein the positive electrode active material oxidizes between 50% and 100% of the copper.

10. O 2 , N 2 3. The method of claim 1 or 2, further comprising adding an additional oxidant to the leaching mixture comprising at least one selected from O, hydrogen peroxide, and peroxodisulfate, optionally adding the additional oxidant to the leaching mixture after the contacting step in which hydrogen gas is generated and the hydrogen gas generation rate has decreased to 10% of the maximum hydrogen gas generation rate during the contacting step.

11. SO 2 , metabisulfite, bisulfite, dithionate, thiosulfate, H 2 O 2 , and H 2 3. The method of claim 1 or 2, further comprising adding a reducing agent to the leach mixture comprising at least one selected from the group consisting of:

12. The acidic aqueous solution is H 2 SO 4 3. The method of claim 1 or 2, further comprising at least one acid selected from the group consisting of methanesulfonic acid and nitric acid.

13. The method according to claim 1 or 2, wherein the acidic aqueous solution has an acid concentration in the range of 18 mol / L to 0.0001 mol / L.

14. 3. The method according to claim 1, wherein the material comprises 0.1% to 10% by weight of copper relative to the total weight of the material.

15. 3. Leaching the material according to claim 1 or 2 to obtain an aqueous solution containing metal ions; and Separating the metal ions to obtain at least one essentially pure metal ion solution and / or at least one essentially pure solid metal ion salt. A method comprising:

16. 1. A method for recycling at least one battery material selected from lithium ion batteries, lithium ion battery waste, lithium ion battery manufacturing scrap, lithium ion cell manufacturing scrap, lithium ion active cathode materials, and combinations thereof, comprising: Optionally, heat treating the at least one battery material at a temperature in the range of 350° C. to 900° C.; mechanically grinding the at least one battery material to obtain a black mass; Optionally, classifying the black mass to obtain a fine fraction and a coarse fraction; and subjecting said black mass, and optionally said fine fraction, said coarse fraction or said fine fraction and said coarse fraction to a leaching process according to claim 1 or 2, A method comprising:

17. 2. A method for leaching a material containing zero oxidation state copper according to claim 1, comprising the steps of contacting the material with an acidic aqueous solution having a pH of less than 6 to form a leaching mixture, and providing a leachate having the formula Li p M q M' r O s wherein M comprises one or more metals selected from nickel, manganese, and cobalt, M' comprises one or more metals selected from Mg, Ca, Ba, Al, Ti, Zr, Zn, Fe, V, Mo, and W, p is in the range of 1 to 1.4, q is in the range of 0.6 to 2, r is in the range of 0 to 1, s is in the range of 2 to 4, and the total amount of copper, in moles, present in the material prior to leaching is divided by the total amount of oxidizing agent, in moles. [0050] is in the range [006] and [0070] is the average oxidation number of M' determined by calculating the molar average of the most stable oxidation number of each metal as an oxide contained in M'.

18. 2. A method for leaching a material containing zero oxidation state copper according to claim 1, comprising the steps of contacting the material with an acidic aqueous solution having a pH of less than 6 to form a leaching mixture, and providing a leachate having the formula Li (1+x) M (1-x) O 2 wherein M comprises nickel and cobalt, x is in the range of 0 to 0.5, and the total amount of copper in moles is divided by the total amount of the cathode active material in moles. [0080] The method is in the range of

Citation Information

Patent Citations

  • Method for leaching valuable metal from anode and cathode active materials of waste lithium ion batteries and removing impurities synchronously

    CN111961839A